Relación entre compromiso organizacional y rotación laboral en colaboradores de organizaciones privadas: revisión aplicada - Chipana Mayekawa, Valeria Midori (2023)
The increase in the voluntary external turnover rate is a phenomenon that keeps rising and has detrimental consequences for business. Organizational commitment is a key factor that influences a worker´s decision to leave the organization when it is not continuously developed. This study aims to analyze the relationship between organizational commitment and voluntary external turnover. An applied review was carried out in the databases Scielo, Proquest and Scopus, selecting the investigations that met the inclusion and exclusion criteria (n=11), following the methodological recommendations of PRISMA guide (Page et al., 2020). The results showed a statistically significant negative correlation with a medium - large effect size, between both constructs. It was discussed the need to address this problem from the Human Resources area through intervention with a comprehensive and preventive approach in order to achieve sustainable change.